Causes for the underreporting of adverse drug events by health professionals: A systematic review - Varallo, Fabiana Rossi [UNESP]; Guimarães, Synara de Oliveira Paim [UNESP]; Abjaude, Samir Antonio Rodrigues [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (FapUNIFESP (SciELO), 2014)
Objective: Identifying the main causes for underreporting of Adverse Drug Reaction (ADR) by health professionals. Method: A systematic review carried out in the following databases: LILACS, PAHO, SciELO, EMBASE and PubMed in the period between 1992 and 2012. Descriptors were used in the search for articles, and the identified causes of underreporting were analyzed according to the classification of Inman. Results: In total, were identified 149 articles, among which 29 were selected. Most studies were carried out in hospitals (24/29) for physicians (22/29), and pharmacists (10/29). The main causes related to underreporting were ignorance (24/29), insecurity (24/29) and indifference (23/29). Conclusion: The data show the eighth sin in underreporting, which is the lack of training in pharmacovigilance. Therefore, continuing education can increase adherence of professionals to the service and improve knowledge and communication of risks due to drug use.
Keywords: Adverse drug reaction reporting systems; Education, continuing; Health personnel; Pharmacovigilance; Product surveillance, postmarketing; Review